Derivation of relations and analysis of tube bending processes using discontinuous fields of plastic strains. Part I. Derivation of geometric-analytic relationships. Part II. Discussion and analysis of the obtained results - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
The generalized strain scheme in bending metal tubes at bending machines with the use of a mandrel presented in Śloderbach (1999; 2002; 20131,2; 2014) satisfies initial and boundary kinematic conditions of bending, conditions of continuity and inseparability of strains. This paper introduces three formal simplifications gradually imposed into forms of principal components of the generalized strain model giving suitable simplifications of the 1st, 2nd and 3rd types. Such mathematical simplifications cause that the obtained strain fields do not satisfy the condition of consistency of displacements and strain continuity. The simplified methods determine safer values of the wall thickness than those from the generalized continuous strain scheme. The condition of plastic incompressibility was used for the derivation of an expression for distribution of wall thickness of the bent elbow in the layers subjected to tension and compression for three examples of discontinuous kinematic strain fields.
Keywords: bending tubes; three simplifications; strains; wall thickness; discontinuous strain fields